2013
DOI: 10.2320/matertrans.m2012390
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an Al Foam/Dense Steel Composite by Friction Welding

Abstract: Al foam is lightweight with superior shock-absorbing properties but has low tensile and bending strengths. This has spurred efforts to form composites of Al foam with dense materials. In this study, we examined the possibility of fabricating composite structures of Al foam and dense steel with strong metal bonding by employing friction welding. The use of friction welding is expected to facilitate the fabrication of Al foam/ dense steel composites by a simple process with low environmental impact. It is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…It is expected that, if an Al foam precursor is placed alternatively to bulk aluminum alloy, the precursor can be easily bonded to the inner wall of the hollow of steel materials by friction welding. By the heat treatment of Al foam precursor-coated hollow steel materials, Al foam core steel composites can be obtained [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that, if an Al foam precursor is placed alternatively to bulk aluminum alloy, the precursor can be easily bonded to the inner wall of the hollow of steel materials by friction welding. By the heat treatment of Al foam precursor-coated hollow steel materials, Al foam core steel composites can be obtained [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus one of the attempts made is to limit the formation of intermetallic compounds to achieve fine joint properties. For AFS panels, Hangai et al (2013) revealed that although the Fe 2 Al 5 and FeAl 3 were generated, the bonding strength of the joint was relatively high compared with that of the aluminum foam with a porosity of approximately 80%.…”
Section: Characteristics Of Aluminized Steel Interfacementioning
confidence: 96%
“…Dissimilar metals weld getting immediate brittle because of its high temperature module of welding zone, inter metallic layer becoming less strength [1]. Welding of aluminium to steel becoming a challenging task, some researches worked on lap joint, T-joint but butt welds in this area have a lack of work, by application criteria the weld of these two metals will reduce fuel consumption in many sectors because of light weight structure without disturbing reliability, stability, operating texture [2][3][4][5]. To overcome the difficulty of weld these metals and to get optimum results researchers worked on many methods like laser welding[6], friction stir welding [7], metal inert gas welding [8], magnetic welding [9], diffusion bonding [10], pressure seam welding [11].…”
Section: Literature Reviewmentioning
confidence: 99%